When a stranger comes to town - Koryta, Michael; Cosby, S. A.; Witt, Amanda Beth; Burke, Alafair; Jain, Smita Harish; Connelly, Michael, 1956-; Freimor, Jacqueline; Lansdale, Joe R., 1951-; Naymark, Emilya; Unger, Lisa, 1970-; Quetermous, Bryon; Jacobs, Tilia Klebenov; et al. (Hanover Square Press, 2021)
It's been said that all great literature boils down to one of two stories--a man takes a journey, or a stranger comes to town. While mystery writers have been successfully using both approaches for generations, there's something undeniably alluring in the nature of a stranger: the uninvited guest, the unacquainted neighbor, the fish out of water. No matter how or where they appear, strangers are walking mysteries, complete unknowns in once-familiar territories who disrupt our lives with unease and wonder. In the newest collection of stories by the Mystery Writers of America, each author weaves a fresh tale surrounding the eerie feeling that comes when a stranger enters our midst, featuring stories by prolific mystery writers such as Michael Connelly, Dean Koontz and Joe Hill.